The Impact of Hotel Tax Revenue in the COVID-19 Era as an Increase in Regional Original Income in Indonesia - Vinda Laurencia Pangkey; Ning Rahayu (Jurnal Public Policy, 2022)
The sharing economy as a new business model is certainly a challenge for the Government to make policies related to this digital transaction. Governments are generally slow to accommodate new business models. On the other hand, sharing economy companies have a great potential as they provide accommodation services. The purpose of this study is to analyze the challenges in increasing the revenue of Local Own-Source Revenue and the revenue opportunities from the expansion of the Hotel Tax Object due to the emergence of various types of sharing economy companies in Indonesia. The method used a qualitative method with data collection through literature study of various publications related to the theme. The results of the study show that in the collection of Hotel Taxes there are challenges in efforts to increase the revenue of Local Own-Source Revenue in Indonesia. First, the impact of Sharing Economy Companies on Hotel Tax Revenue through online platforms can cause a potential tax loss. Second, the impact of the COVID-19 pandemic on hotel industry business activities in the causes of business closures and decline revenue. Furthermore, in the collection of Hotel Taxes, there is an opportunity to increase the revenue of Local Own-Source Revenue in Indonesia, namely (1) the expansion of the Hotel Tax object through the improvement of the Law on Regional Taxes and Regional Levies by considering a new source of Hotel Tax revenue by online platforms in the form of accommodation facilities (2) Providing tax incentives in the form of reduced rates.